The Contribution of Social Media and Mobile Application to Individual Subjective Well-Being in Counseling Perspective - Zadrian Ardi; Indah Sukmawati (RedWhite Press, 2019)
Various researches in information technology, especially in the era of industrial revolution 4.0 have revealed that there has been a major change in the use of wireless devices in the past decade. The high internet usage is directly proportional to the use of social media which is increasing every year. Social media in principle provides various communities in accordance with the purpose and development goals of the platform. This of course will arouse the arena of new problems at the client's life level, thus becoming a challenge for counselors in the era of industrial revolution 4.0. Counselors in this era are required to have a deeper understanding of the root causes that might arise from the online world. Counselors are also required to have special skills in handling individual welfare conditions related to the impact of activities on social media. This study discusses the general impact of social media on individual subjective well-being conditions. This study involved 174 respondents spread throughout the territory of Indonesia by its demography. The results showed that respondents needed mental health interventions through online channels and not in the form of social media.